Methods for estimating forage mass in pastures in a tropical climate - Edvan, Ricardo L. (2019)
There are various methods to estimate the mass production of forage in pastures, but many are not accurate or unsuitable when used with certain species of fodder plants. Therefore, knowing the uses and limitations of the measurement techniques is important. This review aims to report the primary methods of estimating forage mass in pastures in tropical climates. Tropical grasses have the distinctive characteristic of temperate stem elongation, which influences growth and forage quality and may interfere in some techniques used to estimate the forage production. Measurement techniques of forage mass production that consider this variable are important for research and for the farmers in these regions. Among the various direct and indirect methods, the mass of forage grass species is the factor that determines the most appropriate measurement method. Currently, there is no single method that can be used in all situations; thus, knowing the type of biomass that will be evaluated and the best technique for that purpose is critical.